Analisis Tindak Tutur Lokusi, Ilokusi dan Perlokusi pada Film “3.600 Detik” Karya Charon - Simanjuntak, Agnes Abigael; Sagala, Florentina; E Sibuea, Johana Jojor; J Sitorus, Ruth Silvia Lisda; Yuhdi, Achmad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Language is used as a means of communication between users.  Through language, communication between users or speakers can occur well if there is the same understanding between speakers. When someone speaks, there is an interlocutor who will respond to his words. The formulation of the problem that will be discussed is the analysis of speech act events.  This research aims to describe every sentence containing locutionary, illocutionary and perlocutionary events of the characters in the "3600 second film". This research method uses a qualitative descriptive method, namely describing each dialogue delivered by a character. The type of research is literature. The data source in this research is a 3600 second film. Data collection techniques in this research are listening techniques and note-taking techniques. The film depicts how speech act events are conveyed, so that locutionary events are informative, illocutionary events that will have an impact on the listener such as making an offer to the interlocutor and perlocutionary events that are persuasive to experience physical changes that occur in the interlocutor. The results of this research include locutionary, illocutionary and perlocutionary speech acts that are clearly stated.